2012
DOI: 10.1039/c2ob25514f
|View full text |Cite
|
Sign up to set email alerts
|

A novel C,D-spirolactone analogue of paclitaxel: autophagy instead of apoptosis as a previously unknown mechanism of cytotoxic action for taxoids

Abstract: The design, synthesis and biological evaluation of a novel C,D-spirolactone analogue of paclitaxel is described. This is the first paclitaxel analogue without an oxetane D-ring that shows a significant cytotoxic effect (activity one order of magnitude lower than paclitaxel). More importantly, its cytotoxicity is a result of a different mechanism of action, involving mTOR inhibition-dependent autophagy instead of G(2)/M cell cycle arrest-dependent apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Herein we present novel significant findings demonstrating that inhibition of late stage autophagy by BAF-A1 enhanced PBOX-6 but not PBOX-15-induced apoptotic death. Recent studies demonstrated unique autophagy properties endowed by a C, D-spirolactone analogue of paclitaxel not shared with the parent compound highlighting the complexity of autophagy stimulation (43). Inhibition of the early stages of autophagy by 3-methyladenine did not augment PBOX-induced cell death (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…Herein we present novel significant findings demonstrating that inhibition of late stage autophagy by BAF-A1 enhanced PBOX-6 but not PBOX-15-induced apoptotic death. Recent studies demonstrated unique autophagy properties endowed by a C, D-spirolactone analogue of paclitaxel not shared with the parent compound highlighting the complexity of autophagy stimulation (43). Inhibition of the early stages of autophagy by 3-methyladenine did not augment PBOX-induced cell death (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…It results in the inability of chromosomes in achieving a metaphase spindle configuration, and the progression of mitosis and prolonged activation of the mitotic checkpoint triggers apoptosis or reversion to the G-phase of the cell cycle without cell division . This arrests the G2/M cell cycle, and the ratio of large cells is increased and the size distribution might be enlarged in paclitaxel-treated cells . Preventing polymerization of actin filaments might influence the tension of the cytoskeleton than prevent depolymerization because the cytoskeletal framework remains after drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…42 This arrests the G2/M cell cycle, and the ratio of large cells is increased and the size distribution might be enlarged in paclitaxel-treated cells. 43 Preventing polymerization of actin filaments might influence the tension of the cytoskeleton than prevent depolymerization because the cytoskeletal framework remains after drug treatment. Therefore, Lat A had a greater impact on the cell deformability in comparison to Pax, and they have different polymerization and depolymerization targets.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Recently, a C,D-spirolactone taxane (5) was reported to be able to stabilize MT (only 13 times less active than 1a) and to possess cytotoxic activity against U251 human glioma cells (IC 50 values were in the range of 4-8 μM vs. 0.25-0.5 μM for 1a). 9 In addition, it displayed a mechanistically distinct cytotoxic action in comparison with 1a, involving mTOR inhibition-dependent autophagy instead of the G 2 /M cell cycle block-associated apoptosis, which is the general mechanism of action for most classic MT-stabilizing agents. We hypothesize that the unique C,D-spiro ring in compound 5 would be responsible for its unusual mechanism.…”
Section: Introductionmentioning
confidence: 99%